CONCEPT IN LINGUOCULTUROLOGY AND THE UNIQUENESS OF THE CONCEPT OF “GRATITUDE” - Rakhimova Shakhnoza Juraqulovna (Journal Park Publishing, 2024)
In this article, subjective opinions are expressed about the concept and its function in relation to which sciences, and the role and function of the concept of gratitude in linguoculturology.
Keywords: concept, linguoculturology, shukur, culture, gratitude, speech process, culture of speech.